Aphasia disrupts usual care: the stroke team's perceptions of delivering healthcare to patients with aphasia. Issue 21 (9th October 2021) - Carragher, Marcella; Steel, Gillian; O'Halloran, Robyn; Torabi, Torab; Johnson, Hilary; Taylor, Nicholas F.; Rose, Miranda
Abstract: Purpose: Communication disability, including aphasia, is prevalent in the stroke population and impacts service delivery. This study explored the experiences of the multidisciplinary stroke team in delivering healthcare to patients with aphasia. Materials and methods: A phenomenological approach was used to understand the experiences of delivering healthcare services in the presence of aphasia. Healthcare professionals ( n = 16) were recruited across acute and subacute stroke care, with a range of discipline backgrounds and experience. Participants took part in focus groups and data were analysed using an inductive thematic approach. Results: Five themes were evident: 1) aphasia is time consuming, 2) health professionals do not know how to help, 3) health professionals limit conversations with patients with aphasia, 4) health professionals want to know how to help, and 5) health professionals feel good after successful communication. Conclusions: Aphasia disrupts usual care. Health professionals want to help but are working in a non-optimal environment where communication and patient-centred care are not adequately resourced. A video abstract is available in Supplementary Material . IMPLICATIONS FOR REHABILITATION: Current hospital systems and ward culture make it difficult to offer patient-centred care to patients with aphasia. Health professionals want to help patients with aphasia but are working in an environment where patient-provider communication is not adequately resourced. As a result, health professionals dread, limit or avoid talking with patients with aphasia. Health professionals need support which may include ongoing education and on-the-job training, and a change in ward culture including key performance indicators focusing on patient-provider communication.